Inferior branch retinal arterial occlusion treated with intravitreal triamcinolone: a case report - Pereira, Joana Mendes (2019)
Purpose: To report a case of a 48-year-old female with sudden decrease of visual acuity (VA) in the right eye (RE). Methods: This is a retrospective and descriptive case report based on data from clinical records, patient observation and analysis of diagnostic tests. Results: A 48 year old woman with no relevant personal or family history except for the use of oral contraceptives, presented loss of visual acuity, central and superior scotoma in the right eye. Best corrected visual acuity (BVCA) was 20/32 in the right eye (RE) and 20/20 in the left eye (LE). RE fundoscopy revealed cotton wool spots in the territory of the inferior temporal retinal artery. Optical coherence tomography (OCT) showed increased central macular thickness mainly at the level of the nerve fiber layer. RE fluorescein angiography showed stop of fluorescein at the emergence of the inferior temporal artery.  RE showed a superior altitudinal defect respecting the horizontal meridian. An intravitreal injection of 3.2mg triamcinolone was given within 24 hours. RE BVCA improved up to 20/20-1L at 3 months, with improvement of the visual field defect with time. Conclusion: Intravitreal steroids given within a few hours of the arterial occlusion may limit the spreadout of apoptosis nearby the ischemic areas, limiting visual field and central vision losses.